Дослідження потенціалу рекуперації енергії відпрацьованих газів двигунів технологічного транспорту - Криштопа, С. І.; Сем’янчук, А. І.; Добуш, А. І.; Копильців, Д. В.; Матвієнко, Р. М.; Солярчук, І. М.; Kryshtopa, S.; Semianchuk, A.; Dobush, A.; Kopyltsiv, D.; Matviienko, R.; Solyarchuk, I. (ЦНТУ, 2025)
У статті досліджується питання моделювання та підвищення паливної ефективності силових приводів, що застосовуються на великокубатурних дизельних двигунах в нафтогазовій галузі. Як перспективний напрям модернізації зазначених дизельних двигунів запропоновано використання надкритичних циклів двоокису вуглецю (sCO₂). Проведено аналіз сучасних наукових досліджень і публікацій, присвячених тематиці моделювання силових приводів, а також виявлено ряд невирішених проблем, що стосуються практичного впровадження технології sCO₂ у нафтогазовій промисловості тощо. The article investigates the issue of modeling and increasing the fuel efficiency of power drives used on large-capacity diesel engines in the oil and gas industry. The use of supercritical carbon dioxide (sCO₂) cycles is proposed as a promising direction for the modernization of these diesel engines. An analysis of modern scientific research and publications on the topic of power drive modeling is carried out, and a number of unresolved problems related to the practical implementation of sCO₂ technology in the oil and gas industry are also identified. For this reason, the article considers the potential of using supercritical carbon dioxide (sCO₂), the organic Rankine cycle (ORC) and thermoelectric generator systems (TEG) for waste heat recovery (WHR) of technological transport in the oil and gas industry etc.
Research into the Potential for Energy Recovery from Exhaust Gases from Technological Transport Engines
Keywords: транспорт; двигун; моделювання силових приводів; утилізація відпрацьованого тепла; transport; engine; powertrain modeling; waste heat recovery